2011
DOI: 10.1111/j.1525-1470.2011.01493.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential Barriers to Adherence in Pediatric Dermatology

Abstract: This study sought to identify barriers to treatment in children with chronic inflammatory skin disease, particularly those with atopic dermatitis, psoriasis, and acne vulgaris. Caregivers of 101 patients seen in the Children's Specialty Group Division of Dermatology, Children's Hospital of The King's Daughters, Norfolk, Virginia, completed an 11-item Likert scale questionnaire. This survey addressed complexity and time requirements for treatment, medication cost, vehicle formulation, perceived safety, and care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 11 publications
0
32
0
Order By: Relevance
“…In the quantitative literature, there is also more information on topical corticosteroid use than emollient use,14–18 although one study found that most carers of children with eczema did not believe that emollients prevented flare-ups, even after receiving instruction about this in secondary care 19…”
Section: Introductionmentioning
confidence: 99%
“…In the quantitative literature, there is also more information on topical corticosteroid use than emollient use,14–18 although one study found that most carers of children with eczema did not believe that emollients prevented flare-ups, even after receiving instruction about this in secondary care 19…”
Section: Introductionmentioning
confidence: 99%
“…Actual side effects experienced have been suggested to have less of an impact on adherence than parental anticipation or fears of side effects especially with newly prescribed medicines 5. Research into children with skin conditions, such as acne vulgaris and atopic dermatitis, suggests that caregivers may not always know as much as they think they do about how to manage their child’s condition 6. With adherence accurately predicted by caregiver knowledge and beliefs, detailed step-by-step plans should be given to caregivers explaining how, why and when they should treat their child 6.…”
Section: Caregiver Factorsmentioning
confidence: 99%
“…Research into children with skin conditions, such as acne vulgaris and atopic dermatitis, suggests that caregivers may not always know as much as they think they do about how to manage their child’s condition 6. With adherence accurately predicted by caregiver knowledge and beliefs, detailed step-by-step plans should be given to caregivers explaining how, why and when they should treat their child 6. Caregivers also have to accept that their role should be fluid, moving from primary responsibility holder to more of a facilitator in the adolescent years.…”
Section: Caregiver Factorsmentioning
confidence: 99%
“…Even if patients with atopic dermatitis do fill the prescription, adherence may still be poor, with a mean adherence rate of only 40% for five days and 32% for eight weeks [4,5]. Non-adherence may be related to forgetfulness, the time consuming nature of topical treatment, financial burden, lack of a trusting physician-patient relationship, dislike of the prescribed vehicle, steroid phobia or other fears, or a lack of understanding about the disease and proper application of medication [6]. Some 1 to 3.8 billion dollars per year are spent in the United States for treatment of atopic dermatitis; if patients were more adherent, unnecessary return visits and medication changes could be avoided, and healthcare dollars could be saved [7,8].…”
Section: Introductionmentioning
confidence: 99%